2010
DOI: 10.2967/jnumed.110.076521
|View full text |Cite
|
Sign up to set email alerts
|

Cerenkov Luminescence Imaging of Medical Isotopes

Abstract: The development of novel multimodality imaging agents and techniques represents the current frontier of research in the field of medical imaging science. However, the combination of nuclear tomography with optical techniques has yet to be established. Here, we report the use of the inherent optical emissions from the decay of radiopharmaceuticals for Cerenkov luminescence imaging (CLI) of tumors in vivo and correlate the results with those obtained from concordant immuno-PET studies. Methods: In vitro phantom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
266
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(273 citation statements)
references
References 32 publications
(38 reference statements)
7
266
0
Order By: Relevance
“…Recently, there has been growing interest in the use of photons from Cherenkov radiation for optical imaging [4][5][6][7][8][9][10][11][12] and for excitation of quantum dots and fluorophores in vivo [6,8]. Charged particles such as β + and β − which are generated from radioactive isotope decay can result in visible light with a broad energy range (ca.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been growing interest in the use of photons from Cherenkov radiation for optical imaging [4][5][6][7][8][9][10][11][12] and for excitation of quantum dots and fluorophores in vivo [6,8]. Charged particles such as β + and β − which are generated from radioactive isotope decay can result in visible light with a broad energy range (ca.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analysis showed that both OI and PET displayed good T/N ratios. Examining a range of radionuclides including 18 F, 64 Cu, 89 Zr, 124 I, and 131 I and the a-emitter 225 Ac, Ruggiero et al found that radiance detected by OI and radioactivity detected by PET correlated well in a linear regression model (R 5 0.98 for 89 Zr) (14). They also used a radiolabeled prostate-specific membrane antigen targeting the monoclonal antibody 89 Zrdesferrioxamine B [DFO]-J591 for immuno-PET in LNCaP tumor-bearing mice positive for prostate-specific membrane antigen, and the data correlated well both qualitatively and quantitatively with CLI.…”
Section: Cross Validations Of CLI Petmentioning
confidence: 99%
“…b 1 -emitters include 11 C, 13 N, 15 O, 18 F, 64 Cu, 68 Ga, and 124 I; Robertson et al used 13 N and 18 F to demonstrate CLI (9). On the other hand, 3 H, 14 C, 32 P, 89 Sr, 90 Y, 131 I, and 177 Lu emit principally high-energy b 2 , and the decay of these emitters is often accompanied by g-rays. Importantly, many b 2 -emitters have already been used for treatment of cancer.…”
Section: Recent Advances In Cerenkov Luminescence Imaging (Cli)mentioning
confidence: 99%
See 1 more Smart Citation
“…Cerenkov luminescence imaging (CLI), a newly emerged molecular imaging technology [18][19][20][21][22][23][24][25][26] , harnesses the luminescence generated from the + and -decay of radionuclides such as 18 F and 131 I in the medium. The charged particle (such as + and -) polarizes molecules while it travels in the medium [18][19][20] , and luminescence/light is emitted when the polarized molecules relax back to equilibrium.…”
Section: Introductionmentioning
confidence: 99%